(3Mbhb GdEfSGf (B:s (3GdeaGgje GdCSGSjI hGdLhGfH hGdVhGHW GdJWHjbjI GddGReI dMeGjJgG (B/s - (3YhV, CSGeI eMeO MSfs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3jJfGhd cJGH (B((3Mbhb GdEfSGf (B: (3GdeaGgje GdCSGSjI hGdLhGfH hGdVhGHW GdJWHjbjI GddGReI dMeGjJgG(B) (3hGdPj bGe HJCdjag (B((3CSGeI eMeO MSf YhV(B) (3aj MhGdj (B(110) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3Mbhb GdEfSGf aj GdbGfhf GdOhdj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdebOeI, GdaUd GdChd (B: (3GdeaGgje GdCSGSjI dMbhb GdEfSGf, GdaUd GdKGfj (B: (3GdLhGfH hGdVhGHW GdJWHjbjI GddGReI dMeGjI Mbhb GdEfSGf, GdaUd GdKGdK (B: (3HYV GdJWHjbGJ GdYedjI dMbhb GdEfSGf GdeQJHWI HGdYed GdCefj(B... (3EdN(B.s
(3HHdjhLQGajI (B: (3UaMI (B103-108.s
Keywords: (3Mbhb GdEfSGf (B((3bGfhf Ohdj(B)s; (3GdbGfhf GdOhdjs; (3GdbGfhf GdEfSGfjs; (3Mbhb GdEfSGfs; (3Mbhb GdEfSGfs -- (3bhGfjf hJTQjYGJs